Civil society revisited lessons from Poland - Jacobsson, Kerstin; Korolczuk, Elżbieta (Berghahn, 2017)
In much social scientific literature, Polish civil society is all too often caricatured as weak and passive. This volume offers a much-needed corrective, challenging this characterization on both theoretical and empirical grounds. Focusing on forms of collective action that researchers too often ignore due to their theoretical and methodological blind spots, the studies gathered here show how certain forms of activism and claims are legitimized in public discourse as representing civil society proper, while others are unfairly dismissed. Taken together, they constitute a powerful critique of a model of civil society that is 'made from above' by elites, media, and public institutions
Keywords: Zivilgesellschaft; Polen; Aufsatzsammlung